Pengaruh Persepsi Kemudahan Penggunaan dan Persepsi Kegunaan Terhadap Keputusan Nasabah Menggunakan QRIS Bank BRI Dengan Kepercayaan Sebagai Variabel Intervening - Adrianto, Yuda; Rahmidani, Rose (Universitas Negeri Padang, 2024)
The research aims to analyze the influence of perceived ease of use and perceived usefulness on customer decisions using BRI QRIS with trust as an intervening variable. The number of samples used is 170 samples using the Hair et al. formula.This research uses a purposive sampling technique. The data used is primary data with criteria that have been maintained. The analysis method used is SEM using Smart PLS 4.0. The research results show that although Perceived Ease of Use and Perceived Usefulness have a positive influence on usage decisions, this relationship is not statistically strong. In contrast, the positive impact of both constructs on trust is significant. Specifically, trust functions as a mediator, significantly influencing the relationship between Perceived Ease of Use, Perceived Usefulness, and usage decisions.